Effect of Ocimum sanctum Linn (Tulsi) on the oxidative stability and storage quality of chicken sausages. Issue 4 (13th July 2015) - Bhat, Z. F.; Kumar, Sunil; Kumar, Lokesh
Abstract : Purpose: – The purpose of this paper was to explore the possibility of utilization of Ocimum sanctum Linn (Tulsi) leaf extract as a natural preservative in muscle foods. The products incorporated with Ocimum sanctum leaf extract were assessed for various oxidative stability and storage quality parameters. Design/methodology/approach: – The Ocimum sanctum leaf extract was incorporated at 300 mg/kg level in the formulation. Chicken sausages incorporated with Ocimum sanctum leaf extract along with control samples were aerobically packaged in low-density polyethylene pouches and assessed for lipid oxidation, physicochemical, microbiological and sensory characteristics under refrigerated (4 ± 1°C) conditions. Findings: – Ocimum sanctum leaf extract showed a significant ( p < 0.05) effect on the lipid stability, as the treated products exhibited significantly ( p < 0.05) lower thiobarbituric acid reactive substances (mg malonaldehyde/kg) and free fatty acid (% oleic acid) values in comparison to control. A significant ( p < 0.05) effect was also observed on the microbiological characteristics of the products, as the treated products showed significantly ( p < 0.05) lower values for total plate count, psychrophilic count and yeast and mould count. Significantly, ( p < 0.05) higher scores were also observed for various sensory parameters of the treated products. Originality/value: – The paper has demonstrated the use of Ocimum sanctum leaf extract as a potential natural preservative, as it successfully improved the oxidative stability and storage quality of the products during refrigerated (4 ± 1°C) storage and may be commercially exploited as a natural preservative in muscle foods.